2016
DOI: 10.1108/jd-06-2014-0080
|View full text |Cite
|
Sign up to set email alerts
|

The everyday life information seeking behaviours of first-time mothers

Abstract: The authors are grateful to the mothers and staff from the support group and representatives from the local health and library services, who all very generously shared their time and experiences. Structured AbstractPurpose The study investigates the everyday life information seeking behaviours of first-time mothers, as they encounter new, significant and pressing information needs which arise alongside their new responsibilities.Design/methodology/approach -A qualitative approach, combining narrative interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 34 publications
5
92
0
Order By: Relevance
“…Informational support is critical for mothers preparing for their new life role and to enable them to feel confident in their transition to motherhood (Darvill, Skirton et al ; Leahy‐Warren, McCarthy et al ; Loudon, Buchanan et al ) and, as motherhood develops, so do the information practices of individual mothers (Greyson ). Mothers and mothers‐to‐be have many potential sources of information including family, friends, print and broadcast media, health professionals, digital resources, and other mothers (Berkule‐Silberman, Dreyer et al ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Informational support is critical for mothers preparing for their new life role and to enable them to feel confident in their transition to motherhood (Darvill, Skirton et al ; Leahy‐Warren, McCarthy et al ; Loudon, Buchanan et al ) and, as motherhood develops, so do the information practices of individual mothers (Greyson ). Mothers and mothers‐to‐be have many potential sources of information including family, friends, print and broadcast media, health professionals, digital resources, and other mothers (Berkule‐Silberman, Dreyer et al ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Motherhood is a significant life change that creates information needs across a range of topics and raises new needs regarding support, socialization and relationships (Carolan , Robb, McInery et al ; Loudon, Buchanan et al ). There are many sources of information available to new mothers who have to choose how to use these different sources and which sources to use for which needs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parenting arena is further fraught by multiple sources offering conflicting information and parents' perceptions that their decisions and actions are monitored and judged by others, from health professionals to strangers (O'Brien, Greyson, Chabot & Shoveller, 2018). For example, Loudon, Buchanan and Ruthven (2016) found that parents did not always share information with health professionals for fear of being negatively evaluated. Low-income and young parents may experience additional monitoring due to the threat of child apprehension from social services, making them less likely to trust professionals or to reach out for help when they need it (Romagnoli & Wall, 2004;Walker, 2012).…”
Section: Literature Review Parents' Information Practicesmentioning
confidence: 99%
“…In another study, it has been highlighted the fact that the experiential nature of information received over the network from family members or peers is very much valuated in case of first-time mothers, as they feel the pressure to comply with the social status of "good mother" [Loudon, Buchanan, Ruthven, 2016]. Still, because of this special situation, the behaviour related with the use of information was characterized by tension, conflict and a kind of information overload.…”
Section: Social Network and Social Media Influence Upon Consumer Behmentioning
confidence: 99%